A Perspective Discussion on Rising Pesticide Levels and Colon Cancer Burden in Brazil - Uyemura, Sergio Akira; Stopper, Helga; Martin, Francis L.; Kannen, Vinicius (Frontiers in Public Health, 2017)
Agriculture is a mainstay of many developing countries’ economy, such as Brazil. According to the Food and Agriculture Organization of the United Nations, Brazil is the major global consumer of pesticides. Irrespective of the fact that the International Agency for Research on Cancer suggests that pesticides promote human cancer risk, a prospective study reports that colorectal cancer (CRC) burden will increase in developing countries by approximately 60% in the coming decades. Here, we review the literature and public data from the Brazilian Federal Government to explore why pesticides levels and new cases of colon cancer (CC) are rising rapidly in the country. CC incidence is the second most common malignancy in men and women in the South and the Southeast of Brazil. However, while these regions have almost doubled their pesticide levels and CC mortality in 14 years, the amount of sold pesticides increased 5.2-fold with a corresponding 6.2-fold increase in CC mortality in Northern and Northeastern states. Interestingly, mortality from endocrine, nutritional, and metabolic diseases are rapidly increasing, in close resemblance with the pesticide detection levels in food. Taken together, we discuss the possibility that pesticides might alter the risk of CC.